Las puertas de Levrero - Julio Premat (Cuadernos LIRICO)
The image of the door, either literal or metaphorical, allows us to explore of the fundamental dynamism that characterizes the oeuvre of Levrero and to specify his existential position as author : a writer who finds himself on the threshold of a text to come. In fact, whether it be through the spatial dynamic of the first texts or through the continual mise-en-scène of writing that never ceases to begin, we observe the omnipresent projection of self towards an ideal and chimeric oeuvre of surpassing. In the article, I focus on several texts (El Lugar, Desplazamientos, La Novela Luminosa) to suggest a panoramic view that underlines continuity in places where some have seen full-on rupture. These thematics also allow the illustration of a contemporary obsession with beginnings. In Levrero’s work, a response, already present in the work of Juan Emar and Macedonio Fernández, to the disorientation of current creators crystalizes : to only write beginnings, to focus on a never-realized textual promise that is still being made.